2012
DOI: 10.1103/physrevb.85.155407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light impurities on the electronic structure of copper nanowires

Abstract: Recently an interesting mechanochemical effect was found showing a possibility to produce longer copper atomic chains in nitrogen atmospheres [Amorim and da Silva, Phys. Rev. B 82, 153403 (2010)]. This work presents a systematic and comparative study of the effect of doping with H, B, C, N, O, S, and N 2 impurities to the electronic structure of copper nanowires. It was performed by means of ab initio total energy calculations based on density functional theory, using local density and generalized gradient app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Second, the conductance of the Cu LACs with the N 2 molecule has not yet been determined while the formation of the Cu LACs with light impurities has been discussed from a theoretical viewpoint. 16,17 In the present study, we investigate the conductance and geometry of the Cu atomic junction in a N 2 atmosphere using the MCBJ technique at 10 K. The experimental results indicate the elongation of the Cu atomic junction. Theoretical calculations together with the experimental results reveal formation of the Cu LAC and its structure.…”
Section: ■ Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Second, the conductance of the Cu LACs with the N 2 molecule has not yet been determined while the formation of the Cu LACs with light impurities has been discussed from a theoretical viewpoint. 16,17 In the present study, we investigate the conductance and geometry of the Cu atomic junction in a N 2 atmosphere using the MCBJ technique at 10 K. The experimental results indicate the elongation of the Cu atomic junction. Theoretical calculations together with the experimental results reveal formation of the Cu LAC and its structure.…”
Section: ■ Introductionmentioning
confidence: 95%
“…Metal linear atomic chains (LACs) have attracted much attention owing to their potential application in ultrasmall electronic materials. Especially, fabrication of the metal LACs is the center issue of this field. In recent years, extensive efforts have been made to investigate the fabrication of metal LACs. Yanson et al succeeded in fabricating a gold LAC using the mechanically controllable break junction (MCBJ) technique . Ohnishi et al observed a gold LAC directly through transmission electron microscopy (TEM) .…”
Section: Introductionmentioning
confidence: 99%
“…Adsorbed gas atoms or molecules may cause a deviation from integer values in the conductance at room temperature even at ultrahigh vacuum conditions. For this reason, the influence of light gas atoms and molecules on the structural and electronic properties of metallic junctions and point contacts has been widely studied experimentally [18][19][20][21][22][23][24][25][26][27][28] and theoretically [29][30][31][32][33][34]. For instance, using the MCBJ technique it has been shown that oxygen atoms can be incorporated in noble metal (Au, Ag, Cu) atomic chains, leading to a considerable reduction in conductance for Ag and Cu chains and retaining the conductance near one quantum unit (1g 0 = 2e 2 /h) for Au atomic chains [23,25].…”
Section: Introductionmentioning
confidence: 99%
“…There are little experimental results which directly show the existence of hydrogen on the Au flat surface during the hydrogen evolution reaction. Currently, interaction between metal nanocontact and nitrogen has attracted a lot of interest. When N 2 molecules interact with transition metals, the reactivity of N 2 molecules is enhanced, (e.g., ammonium synthetic reaction). The reactivity of N 2 could be increased further for the metal nanocontact because of the decrease in the number of the neighboring atoms.…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of N 2 could be increased further for the metal nanocontact because of the decrease in the number of the neighboring atoms. The interaction between Cu nanocontact and nitrogen has been investigated using ab-initio calculation. , The calculation result showed a tendency of N and N 2 to make strong bonds in Cu nanocontacts leading to the formation of longer Cu atomic wires. Although the interesting interaction between metal nanocontact and nitrogen was proposed, there has been little experimental investigation on this topic.…”
Section: Introductionmentioning
confidence: 99%